A comparison of techniques for studying oogenesis in the European eel Anguilla anguilla - I. Mazzeo; E. Giorgini; G. Gioacchini; F. Maradonna; M. C. Vílchez; S. Baloche; S. Dufour; L. Pérez; O. Carnevali; J. F. Asturiano (Journal of Fish Biology, 2016)
A multi‐technique approach was used to study the changes occurring in European eel Anguilla anguilla ovaries during hormonally‐induced vitellogenesis. Aside from classic techniques used to monitor the vitellogenic process, such as ovary histology, fat content analysis, sodium dodecyl sulphate–polyacrylamide gel electrophoresis ( SDS–PAGE ) and vitellogenin enzyme linked immunosorbent assay ( ELISA ), a new technique, Fourier‐transform infrared ( FT‐IR ) microspectroscopy, was used to analyse A. anguilla ovaries. The results from the different techniques provided different ways of approaching the same process. Although it is considered a time consuming approach, of all the employed techniques, histology provided the most direct evidences about vitellogenesis. SDS–PAGE and ELISA were also useful for studying vitellogenesis, whereas fat analysis cannot be used for this purpose. The FT‐IR analysis provided a representative IR spectrum for each ovarian stage (previtellogenic stage, early vitellogenic stage, mid‐vitellogenic stage and late vitellogenic stage), demonstrating that it is a valid method able to illustrate the distribution of the oocytes within the ovary slices. The chemical maps obtained confirmed changes in lipid concentrations and revealed their distribution within the oocytes at different maturational stages. When the results and the accuracy of the FT‐IR analysis were compared with those of the traditional techniques commonly used to establish the vitellogenic stage, it became evident that FT‐IR is a useful and reliable tool, with many advantages, including the fact that it requires little biological material, the costs involved are low, analysis times are short and last but not least, the fact that it offers the possibility of simultaneously analysing various biocomponents of the same oocyte.